Analysis of Common Interference in Home WI-FI Networks in RT 6 RW 2, Lawangan Daya Sub-District, and Efforts to Address It (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
WI-FI network problems at home remain a common challenge often experienced by a number of users, especially in densely populated residential areas. This study aims to explain the various types of problems that often arise in domestic WI-FI networks in areas such as RT 6/RW 2, Lawangan Daya Village, as well as to identify corrective measures that can be taken by users. The analysis process was carried out by examining literature sources that discuss router performance, surrounding conditions, and usage methods that can affect network stability. The findings of the study reveal that WI-FI problems are usually triggered by several reasons, including interference from nearby houses, the router's suboptimal position, device weaknesses, and the simultaneous use of many devices. In addition, imperfect router settings also contribute to a decline in connection quality. Referring to these findings, several recommended steps to overcome this problem include rearranging the router position, selecting channels with minimal interference, updating the device system, and using additional tools such as repeaters or WI-FI mesh networks. Overall, this study offers practical insights into the elements that influence home Wi-Fi network quality and provides solutions that can be implemented without requiring significant modifications to the network structure.
Keywords: Keywords: WI-FI Network Interference, Home WI-FI Network, Signal Interference, Quality of Service (QoS), WI-FI Network Management Efforts.